Service quality and patient satisfaction with private health care services in Albania - Rezarta Kalaja; Sllavka Kurti; Redi Myshketa (Intelektual Pustaka Media Utama, 2023)
Hospital service in Albania is facing difficult challenges, always trying to evolve and reform not only related to the high demand for improvement on the available infrastructure and technology, but also due to the private hospital services competition in keeping medical staff and patients with the obligation to ensure quality care, as a fundamental human rights requirement. The purpose of this study is to make an overall assessment regarding the quality of health care in the private sector in Albania and patient satisfaction related to this service. This paper also aims to determine the main factors that play a role in patient satisfaction, and their level of importance, to provide appropriate recommendations that will support the improvement of the quality of service and increasing patient satisfaction in this sector. The instrument used for quality assessment is SERVQUAL, with five main dimensions selected (responsiveness, reliability, safety, tangibles and empathy). Data processed for 400 interviewed patients shows the correlation of patient satisfaction with only four of the elements considered. Hence, the results obtained will back applicable recommendations for developing quality and increasing patient satisfaction.